PEMAKAIAN BAHASA DI RUANG PUBLIK KOTA MEDAN - Amran Purba (MEDAN MAKNA: Jurnal Ilmu Kebahasaan dan Kesastraan, 2019)
Use of language continues to evolve in accordance with the domain and the development is in line with the progress of time. The same thing with the use of language in public spaces in the city of Medan needs to be examined because the language is already disturbing the public. This study was conducted in accordance with the principal task of the Agency and the Center for English Language North Sumatra. This research was conducted with the survey and descriptive method to obtain factual data. This research technique using the technique of shooting and recording data. This study shows the data of concern about the use of language in public space field that includes the language and the use of foreign languages on (1) the nameplate government and private institutions, (2) a shopping center, (3) venue, (4) residential compound and (5) advertising and fabric ranges.